Lecturers' Attitude in Teaching Foreign Cultural Values in English Language Classroom: Balancing Global Perspectives and Local Identity - Puspitasari, Rianny; Devi, Anit Pranita; Dewi, Shafira Anastasya (Institut Agama Islam Negeri Palopo, 2024)
This research aimed to explore lecturers' attitudes and the challenges faced in teaching foreign cultural values in English language learning. This research employed descriptive qualitative and hermeneutic phenomenological designs in which the research instruments used were documentation, observation, and interview. This research involved lecturers of the English Literature study program of one private university in Indonesia. The results of the data analysis showed that the lecturers' attitudes towards teaching foreign cultural values in English language learning varied. However, in general, the majority of lecturers realize the importance of integrating foreign cultural values (in this case English culture) as part of English language teaching and choose to modify materials about conflicting English cultural values. They argued that providing information about foreign cultural values that conflict with local culture is still important, but it should be accompanied by reinforcement that these values do not follow Indonesian culture. The challenges reported by the lecturers included the difficulty of finding sufficiently representative and up-to-date reference sources, the use of authentic materials that require lecturers to deliver content that contains negative cultural values or is contrary to local culture, and the strengthening of national values and local culture so that students are not easily exposed to foreign cultural values. From the student side, the challenges were the lack of motivation, learning ethos, and English skills when understanding English-language reference sources. Future researchers are advised to expand the study of the impact of using authentic materials containing foreign cultural values on student perceptions and attitudes.